The Continuity of Change in the HMI Movement in West Sumatra During the New Order Era - Wulandari Nurul Utami; Erman Erman; Nurus Shalihin (UNIVERSITAS MUHAMMADIYAH METRO, 2027)
This study aims to explore the continuity of change in the HMI movement in West Sumatra during the New Order era. The method used in this study is the historical method with heuristic, source criticism, interpretation, and historiography stages. The data in this study was obtained through: First, interviews conducted with HMI activists who were active during the New Order period in Padang, Bukittinggi, and Batusangkar. Second, archives obtained from HMI elders in West Sumatra, 1998 newspaper archives containing news about HMI in Padang obtained through archives in the Singgalang Daily. Third, books and journal articles related to the research. This study found: First, the value of the HMI movement in West Sumatra during the New Order period. Second, the strategies of the HMI movement in West Sumatra during the New Order period. Third, the patterns of the HMI movement in West Sumatra during the New Order period. This research shows that HMI in West Sumatra during the New Order era was never quiet, with movements that contained continuity of change, values, strategies, and various patterns of movement.